The assessment of knowledge and attitudes of parents of hospitalized children about febrile convulsions: a pilot study - Giannakopoulou, Margarita; Tamvaki, Eleni; Papathanassoglou, Elizabeth; Matziou, Vasiliki N.; Galetseli, Marianthi (My University, 2011)
Background: Febrile convulsions (FC) are common during childhood and have a good prognosis, although they cause fear and anxiety in parents. Aim: (a) To translate the KACP questionnaire into the Greek language and to assess the reliability and validity of the Hellenic version in a population of Greek parents, and (b) to assess Greek parental beliefs, knowledge, attitudes, concerns and practices concerning FC. Method: A pilot study employing a descriptive, corelational design was conducted in two children's hospitals in Athens, from September to November 2008. Data were obtained from a sample of 132 parents of hospitalized children. Translation of the KACP questionnaire from English, back-translation and assessment of validity by an experts group were performed. Internal consistency reliability analyses (Cronbach' sa), test-retest reliability analyses (McNemar test), descriptive statistics and chi - square test, were carried out by the use of SPSS 13.0, using a significance level of a=0.05. Results: The response rate was 88% (132/150 parents). Cronbach'sa was estimated asa=0.71, and test-retest reliability was k=0.99 (McNemar test p>0.05). The mean age of the respondents was 37.77.37 years, 72.7% were female, 90.2% were from a two-parent family structure, 59.2% were high school graduates and 10.6% had previous experience with FC in their child. Greek parents, who comprised 86% of the sample, appeared to recognize the fever as a cause of convulsions and they could distinguish FC from epilepsy (73.5%). On the other hand they had the mistaken beliefs that FC could cause brain damage (90.1%), that the body temperature should be assessed frequently (84.1%) and that lumbar puncture was not an applicable investigation (45.5%). They expressed concern mainly about the outcome: brain damage (65.2%), epilepsy (54.6%), further seizure attacks (68.9%) and death (59.1%). Inappropriate practices that they reported using were to pry the convulsing child's clenched teeth apart and put something in his/her mouth (59.1%) and to restrain the child (67.4%). The family structure (p=0.011), the educational level (p=0.012) and previous experience of FC in their child (p=0.021) partly affected the parental knowledge, attitudes and practices. Conclusions: The results of this pilot study support the reliability and applicability of the KACP questionnaire in a Greek parental population. Further confirmation of its validity is required. Greek parents may need further information and training for better management of their children with FC at home.
Keywords: Childhood; Febrile convulsions; Management; Paternal knowledge; Treatment